Investigation on Processing Maps of Diffusion Bonding Process Parameters for Ti-6Al-4 V/AISI304 Dissimilar Joints. (12th October 2021) - Arun Negemiya, A.; Shankar, A. N.; Guruprasad, B.; Prakash, B.; Dineshkumar, S.; Batu, Areda; Rajakumar, S.
Abstract : The diffusion bonding (DB) method is used in this investigation to connect high-temperature dissimilar materials. The existence of difficult-to-remove oxide coatings on the titanium surfaces, as well as the arrangement of breakable metallic interlayers and oxide enclosures inside the bond region, provides the most significant challenges during the transition from AISI304 to Ti-6Al-4V alloying. In addition, an effort was made to advance DB processing maps for the operational connection of Ti-6Al-4V to AISI304 alloys to improve their performance. Joints had been created by combining several process factors, such as bonding temperature (T), bonding pressure (P), and holding time (t), to create diverse designs. Based on the findings, database processing maps were created. This set of processing maps may be used as a rough guideline for selecting appropriate DB process parameters for generating virtuous excellent bonds between Ti-6Al-4V and AISI304 alloys. The maximum lap shear strength (LSS) was achieved at 800°C, 15 MPa, and 45 min.